2017
DOI: 10.1007/s10460-017-9816-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable palm oil as a public responsibility? On the governance capacity of Indonesian Standard for Sustainable Palm Oil (ISPO)

Abstract: own targets and solving palm-oil related problems, such as deforestation, biodiversity loss, greenhouse gas emissions, and social conflicts between big plantations and local communities. The main governance challenge regards combining a more authoritative implementation mechanism with a convincing balance between sustainability objectives and economic interests of the sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 33 publications
2
78
0
9
Order By: Relevance
“…Currently, about 20% of the global palm oil volume is RSPO certified, meaning that it is produced according to the RSPO sustainability guidelines (RSPO, 2013). Triggered by the influence of the RSPO, Indonesia and Malaysia created their own sustainability guidelines: the voluntary Malaysian Sustainable Palm Oil standard (MPOCC, 2018), and the mandatory Indonesian Sustainable Palm Oil certification scheme (Hidayat et al, 2018). Like the RSPO, these standards focus on legality, good agricultural practices, and some form of environmental sustainability.…”
Section: Palm Oil Production and Sustainabilitymentioning
confidence: 99%
“…Currently, about 20% of the global palm oil volume is RSPO certified, meaning that it is produced according to the RSPO sustainability guidelines (RSPO, 2013). Triggered by the influence of the RSPO, Indonesia and Malaysia created their own sustainability guidelines: the voluntary Malaysian Sustainable Palm Oil standard (MPOCC, 2018), and the mandatory Indonesian Sustainable Palm Oil certification scheme (Hidayat et al, 2018). Like the RSPO, these standards focus on legality, good agricultural practices, and some form of environmental sustainability.…”
Section: Palm Oil Production and Sustainabilitymentioning
confidence: 99%
“…Nevertheless, compared to other private sustainability standards for palm oil, the ISPO is seen as deficient as it provides very little protection of human rights and community livelihoods (McInnes, 2017); has less ambitious goals, particularly related to forest conservation (Pirard et al, 2017); and has not yet developed its full potential because of weak authority of the implementing organisations, and lack of acceptance and reliability in the global market (Hidayat, Offermans, & Glasbergen, 2017). More criticism has emerged as there are none of the sustainability standards required for corporations to strengthen indigenous institutions; to encourage independent unions, or provide assistance for the independent smallholders to develop production on their own land autonomously.…”
Section: ) the Totalmentioning
confidence: 99%
“…Study has suggested that private and public initiatives need to diversify their implementation approach to accommodate the different types of smallholders (Hidayat et al, 2017).…”
Section: Indonesian Palm Oil Sector and Ispomentioning
confidence: 99%
See 2 more Smart Citations